An efficient multi-stage optimization approach for damage detection in plate structures. (October 2017) - Dinh-Cong, D.; Vo-Duy, T.; Ho-Huu, V.; Dang-Trung, H.; Nguyen-Thoi, T.
Highlights: An efficient multi-stage optimization approach for damage detection in plate-like structures is proposed. Damage identification process is achieved by minimizing an objective function via flexibility changes of the structure. A modified differential evolution (MDE) algorithm is used for many stages of damage detection. Low damage variables in each stage are eliminated after several generations. Proposed method is not only successful for damage detection but also shows the efficient computational cost. Abstract: The paper presents an efficient multi-stage optimization approach for damage detection in plate-like structures. In this approach, the damage identification process is achieved by minimizing an objective function established via flexibility changes of the structure. The vector of design variables represents correspondingly the damage extent of elements discretized by the finite element model. For analyzing the response of plate structures, the finite element model using 9-node quadratic quadrilateral elements is applied. For solving the optimization problem, a modified differential evolution (MDE) algorithm, which can help enhance the balance of global and local searches in each generation, is used for many stages of damage detection, in which the low damage variables in each stage are gradually eliminated after several generations to reduce the dimension of searching space and to increase the convergence rate of the problem. The efficiency of the proposed method is investigated through two numerical examples for isotropic and laminated composite plates. The obtained results indicate that the proposed method not only successfully detects the location and severity of multi-damage cases in the plate structures, but also show the better efficiency in term of computational cost.